اضطرابات الشحوم عند مريضات متلازمة المبيض عديد الكيسات - سلمان, ربا; خياط, محمد; موسى, ربا (Latakia University Journal -Medical Sciences Series, 2019)
Introduction: The prevalence of Polycystic ovary syndrome is4-12% of Premenopausal women. It is described as the presence of endocrine and metabolic disorders Which may lead to an early development to CVD. Aim: screen for dyslipidemia in patients with PCOs and to study the relationship between lipids and age, Waist circumference WC, Body mass Index BMI and Fasting Glucose Fglu. Materials and Methods: 105 patients were included during the period from February 2018 till January 2019. We studied dyslipidemia distribution according to phenotype. Results: Prevalence of dyslipidemia was 60%. We found low HDL-c and elevated TC, LDL-c and TG. The first phenotype was the most prevalent in which low HDL-c was the most prevalent then elevated LDL-c, TC and TG. Third phenotype was the third in prevalence with dyslipidemia resemble to the first phenotype. The second phenotype was the third in prevalence in which elevated LDL-c and TG were the most prevalent then low HDL-c and elevated TC. The fourth phenotype was the least prevalent in which low HDL-c and elevated LDL-c. We found significantly negative correlation between HDL-c and WC and BMI and significantly positive correlation between LDL-c and age, WC, BMI and Fglu. Conclusion: It is important to screen for dyslipidemia in PCOs patients مقدمة: يقدر نسبة انتشار متلازمة المبيض عديد الكيسات PCOS بحوالي 4-12% من النساء في سن النشاط التناسلي وتتصف بوجود اضطرابات غدية صماوية واستقلابية مما يجعل النساء المصابات بهذه المتلازمة أكثر عرضة وبشكل باكر للأمراض القلبية الوعائية. هدف البحث: الكشف عن وجود اضطراب في مستويات الشحوم عند مريضات PCOS ودراسة علاقة مستويات الشحوم مع كل من: العمر ومحيط الخصرWC ومشعر كتلة الجسمBMI ومستوى سكر الدم الصيامي Fglu. طرائق البحث: شملت عينة الدراسة 105مريضة PCOs من المراجعات لمشفى تشرين الجامعي بين شباط 2018م ولغاية كانون ثاني 2019م تم دراسة توزع اضطراب الشحوم حسب النمط الظاهري. النتائج: بلغت نسبة انتشار اضطراب الشحوم 60% من العينة وجدنا انخفاض الـ HDL-c وارتفاع الـ LDL-c والـ TC والـ TG. وجدنا أن النمط الأول هو الأكثر شيوعاً بنسبة 61% واضطراب الشحوم الأكثر مشاهدة فيه هو انخفاض الـ HDL-c يليه ارتفاع الـ LDL-c ومن ثم ارتفاع الـ TC وآخراً ارتفاع الـ TG . يليه النمط الثالث مع اضطراب شحوم مماثل للنمط الأول. النمط الثاني بالمرتبة الثالثة من حيث الانتشار وفيه وجدنا أن ارتفاع الـ LDL-c والـ TG هما الأكثر مشاهدة يليهما انخفاض الـ HDL-c وارتفاع الـ TC. النمط الرابع الأقل انتشارا وكان فيه انخفاض الـ HDL-c وارتفاع الـ LDL-c بنسب متساوية، وجدنا علاقة عكسية هامة بين الـ HDL-c وWC وBMI وعلاقة ايجابية هامة بين الـ LDL-c والعمر وWC وBMI وFglu. الخلاصة: من الضروري التحري عن اضطرابات الشحوم لدى مريضات PCOs.